2014
DOI: 10.1124/mol.114.094185
|View full text |Cite
|
Sign up to set email alerts
|

Phage Display–Mediated Discovery of Novel Tyrosinase-Targeting Tetrapeptide Inhibitors Reveals the Significance of N-Terminal Preference of Cysteine Residues and Their Functional Sulfur Atom

Abstract: Tyrosinase, a key copper-containing enzyme involved in melanin biosynthesis, is closely associated with hyperpigmentation disorders, cancer, and neurodegenerative diseases, and as such, it is an essential target in medicine and cosmetics. Known tyrosinase inhibitors possess adverse side effects, and there are no safety regulations; therefore, it is necessary to develop new inhibitors with fewer side effects and less toxicity. Peptides are exquisitely specific to their in vivo targets, with high potencies and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…Lee et al . () demonstrated that the ability of tetra‐peptides to bind tyrosine may be related to the presence of cysteine at the N‐terminal position. Peptides with cysteine located at the N‐terminus showed better ability to inhibit tyrosinase than peptides with cysteine located at the C‐terminus.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al . () demonstrated that the ability of tetra‐peptides to bind tyrosine may be related to the presence of cysteine at the N‐terminal position. Peptides with cysteine located at the N‐terminus showed better ability to inhibit tyrosinase than peptides with cysteine located at the C‐terminus.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, for the purpose of developing a safe and effective skin-whitening agent, we screened about 400 natural products from 78 different of Chinese herbal plants for compounds with inhibitory activity against mushroom tyrosinase. The natural compound T1 isolated from Gastrodia elata shows outstanding inhibitory potency against tyrosinase (IC 50 = 0.53 μM, K i = 58 ± 6 nM), which is more effective than β-arbutin, kojic acid, short peptides 74 75 and other known natural compounds ( Supplementary Table S1 ). Our docking model demonstrates that the sulfur atom of T1 makes close contacts with the copper ions in the active site of tyrosinase ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Combinatorial phage-displayed random peptide libraries are very valuable tools for studying the interaction between peptides and other substances (or materials). In the past, scientists have been focused on identifying B/T cell epitopes [11][12][13][14][15][16][17][18][19], disease-specific antigen mimics [22][23][24][25][26][27][28][29][30][31][32][33][34], receptor agonists/antagonists [35][36][37][38][39][40][41][42][43][44][45], enzyme inhibitors [48][49][50][51][52][53][54] and protein partners [55][56][57][58][59][60][61][62]. In recent years, there is an increasing number of researchers who apply this technique to new areas ...…”
Section: Discussionmentioning
confidence: 99%
“…TIMP-2 is a broad range inhibitor of matrix metalloproteinases (MMPs) [51]. In addition to protease inhibitors, peptide-based inhibitors against various enzymes, such as human HMG-CoA reductase [52], ubiquitin ligases [53], and tyrosinase [54], have all been identified by phagedisplayed random peptide libraries.…”
Section: For Enzyme Inhibitorsmentioning
confidence: 99%